Funciones desempeñadas como analista de créditos pyme en la cooperativa de ahorro y crédito León XIII – agencia Huamachuco – año 2018 - Ruiz García, Yhordan César (2020)
The present adequacy work report had the general objective of proposing a new design of the incentive program to improve the retention of credit analysts in COOPAC León XIII - Huamachuco Agency, 2018; for which we have proceeded to analyze the reality of the company and identify the causes that originate it. To later establish alternative solutions. Among the main problems identified, there is the migration of credit analysts to other financial institutions, and customers also leave with them; Likewise, it was found that the incentive plan that allows loyalty of credit analysts has not been updated. In order to provide solutions to the problems identified, it was proposed to develop an incentive program that is in accordance with the labor market and is fair for everyone, in such a way that it motivates them to remain in the entity fulfilling their functions. Likewise, regarding the diagnosis of the professional training given in the School of Administration, it was found that a good level of knowledge is offered to be able to satisfactorily perform the positions held; however, it is necessary to incorporate academic improvements, to further strengthen the practical part of the courses, and also to incorporate other courses and workshops that are more useful in professional life.